High performance hierarchical torus network under matrix transpose traffic patterns - Rahman, M.M. Hafizur; Susumu, Horiguchi (2004)
Interconnection networks play a crucial role in the performance of massively parallel computers. Hierarchical interconnection networks provide high performance at low cost by exploring the locality that exists in the communication patterns of massively parallel computers. A Hierarchical Torus Network (HTN) is a 2D-torus network of multiple basic modules, in which the basic modules are 3Dtorus networks that are hierarchically interconnected for higher level networks. The static network performance of the HTN has already been studied and has been shown to be good. Dynamic communication performance has been evaluated under uniform trafﬁc patterns but not under a nonuniform trafﬁc, such as matrix transpose trafﬁc patterns. In this paper, we present a deadlock-free routing algorithm for the HTN using virtual channels and evaluate the network’s dynamic communication performance under matrix transpose trafﬁc, using the proposed routing algorithm. We evaluate the dynamic communication performance of HTN, H3D-mesh, TESH, and mesh networks by computer simulation. We ﬁnd that the dynamic communication performance of HTN is better than that of the H3D-mesh, TESH, and mesh networks.